The Effects of Growing Groups and Scarcity on the Use of a Common Pool Resource – a Lab-in-the-Field Experiment with Lake Victoria Fishers - Astrid Dannenberg; Charlotte Klatt; Pia Pico (Environmental and Resource Economics, 2024)
Abstract Using a lab-in-the-field experiment with Ugandan fishers, we study if and how the use of a common pool resource changes when the resource is either scarce or abundant and when the number of users increases over time. Both resource scarcity and a growing group require users to be more constrained, that is, more cooperative, in order to maintain the resource. However, the results show that fishers do not curtail their harvesting behavior under increased pressure, leading to rapid overexploitation when scarce resources are used by a growing group. This implies a particular need for sustainable management when scarce resources are exposed to in-migration.
Additional information: C90;D90;Q22
Keywords: 330; Resource scarcity; Group growth; Common pool resources; Cooperation; Lab-in-the-field experiment